Digital Terrain Modeling: Principles and Methodology - Li, Zhilin (CRC Press, 2009)
Digital terrain models have found wide applications in disciplines such as mapping, remote sensing, civil engineering, mining engineering, geology, geomorphology, military engineering, land planning, and communications. Digital Terrain Modeling: Principles and Methodology is the only authored book to provide comprehensive coverage of recent developments in the field. The volume includes an examination of data acquisition and a review of the presentation of DTMs in databases, in contour form, and in various forms of computer graphics. It explores the theories, methods, and algorithms of digital terrain modeling, and focuses on quality control and accuracy. This book discusses extensions of digital terrain models for specific problems and anticipates where this research will lead.